Mast cell deficient and neurokinin-1 receptor knockout mice are protected from stress-induced hair growth inhibition - Arck, Petra C.; Handjiski, Bori; Kuhlmei, Arne; Peters, Eva M. J.; Knackstedt, Maike; Peter, Anita; Hunt, Stephen P.; Klapp, Burghard F.; Paus, Ralf (Journal of molecular medicine (Berlin, Germany), 2005)
Despite the lack of insight on distinct mediators in the skin orchestrating the pathophysiological response to stress, hair loss has often been reported to be caused by stress. Recently we revealed the existence of a "brain-hair follicle axis" by characterizing the neurokinin (NK) substance P (SP) as a central element in the stress-induced threat to the hair follicle, resulting in premature onset of catagen accompanied by mast cell activation in the skin. However, our understanding of possible SP-mast cell interactions in the skin in response to stress was limited since the receptor by which SP activates skin mast cells and the extent of mast cell mediated aggravation of SP remained to be elucidated. We now employed NK-1 receptor knockout mice (NK-1R(-/-)) and mast cell deficient W/W(v) mice and observed that stress-triggered premature induction of catagen and hair follicle apoptosis does not occur in NK1(-/-) and W/W(v) mice. Furthermore, the activation status of mast cells was less in stressed NK1(-/-) mice than in wild-type control. Additionally, stress-induced upregulation of SP positive nerve fibers was absent in both NK-1R and W/W(v) mice. These results indicate that the cross-talk between SP and mast cell activation via NK-1R appears to be the most important pathway in the regulation of hair follicle cycling upon stress response.